Antibacterial Potential of Radish Extract (Raphanus sativus L.) Against Fish Spoilage Bacteria - EVELINE EVELINE; CHIKITA WINI TANUMIHARDJA (Indonesian Society for microbiology, 2019)
Radish (Raphanus sativus L.) root is commonly used as flavor enhancing additive or side dish. Previous research revealed the presence of active compound in which could inhibit bacterial growth. Thus, a research concerning natural antibacterial for fish products that are categorized as high-risk food being contaminated by spoilage bacteria (Pseudomonas aeruginosa, Bacillus cereus, dan Staphylococcus aureus) was done. Radish root extraction was made by using ethyl acetate (semi polar) for 3 days. Well diffusion was performed using 4 extract concentration (10, 20, 30, dan 40% (w/v)) againts three fish spoilage bacteria. Based on our results, 30% concentration was the best concentration which inhibit more than 10 mm in inhibition zone with MIC and MBC. The scores were of 0.06% and 0.24% (P. aeruginosa), 0.13% and 0.50% (S. aureus), and 0.12% and 0.48% (B. cereus). Moreover, based on stability test against heating temperature showed that this extract concentrationwas more stable in 80°C with duration times for 5 minutes and pH 3 which resulting the lowest inhibition zone reduction compares to control extract. Radish extract was categorized as low toxic compound (LC50 = 839.52 ppm) functioning in antibacterial compound containing major antibacterial compound (bis(2-ethylhexyl) phthalate, 1,2-benzenedicarboxylic acid, 9,12,15-octadecatrienoic acid), fatty acid (n-hexadecanoic acid, butanedioic acid), carboxylic acid (isobutyric acid, malic acid, oleic acid), and minor antibacterial compound (n-Hydroxymethylacetamide, 2,4-bis(1,1-dimethylethyl), 2,4-pentanedione,2-Cyclohexen-1-one, hydrazine, cyclohexene oxide, gamma-sitosterol).